Pengaruh Hasil Pendidikan Karakter Terhadap Kecerdasan Interpersonal Siswa SMP - Samosir, Teresia Tina; Sinaga, Juster Donal (Universitas Sanata Dharma, 2019)
This study aims to (1) describe SMP Santo Aloysius Turi Yogyakarta grade VIII students' achievement in character education in 2018/2019 academic year; (2) describe SMP Santo Aloysius Turi Yogyakarta grade VIII students' interpersonal intelligence in 2018/2019 academic year; (3) describe how students' performance in character education subject influences their interpersonal intelligence. This is a quantitative study with 31 grade VIII students of SMP Santo Aloysius Turi Yogyakarta 2018/2019 academic year as the subject. The data was collected through Movie Based Character Education Achievement Test which consisted of 88 multiple choices questions and Interpersonal Intelligence Questionnaire which consisted of 32 items. The reliability coefficient formula used was Alpha Cronbach (?) which was 0,933 for the Movie Based Character Education Achievement Test and 0,921 for Interpersonal Intelligence Questionnaire. The data were analyzed using simple linear regression and descriptive statistical categories which were very high, high, medium, low, and very low. The results showed that (1) all participants of the study (100%) performed well in the Movie Based Character Education Achievement Test; (2) 18 students (58%) showed that they had very high interpersonal intelligence, 11 students (35,5%) showed high interpersonal intelligence, two students (6,5%) showed medium interpersonal intelligence; (3) the result of the character education test did not significantly influence students' interpersonal intelligence. However it had positive effect. Meanwhile, the students' character education test result (X) influenced students' interpersonal intelligence (Y) as much as 0,3%, with the statistical significance score of 0,780 0,05.